Association between Maternal and Neonatal Blood Pressure - Elaheh Amini; Firouzeh Nili; Fatemeh Nayeri; Mahmood Behpour; Mamak Shariat; Tahereh Esmaeilnia (Tehran University of Medical Sciences, 2010)
Objective: This study aims to describe the blood pressure profile of newborns of preeclampsia mothers in Vali-e-Asr hospital during 2003-2004. Materials and methods: In this cross-sectional descriptive analytical study 200 mothers and their newborns were studied. Blood pressure of all newborns was checked by oscillometric method on the first day after birth and recorded in a questionnaire along with information pertaining to the mother, obtained by interview or through medical file retrieval. Results: The newborns of mothers with high systolic (>140 mmHg) and diastolic (>90 mmHg) blood pressure had mean systolic (65.40 mmHg) and diastolic (42.85 mmHg) blood pressures higher than that in neonates of normotensive mothers( P <0.006). Mean systolic and diastolic blood pressure of neonates whose mothers were preeclampsia (68.2/42.11 mmHg or chronically hypertensive (68.59/ 41.50 mmHg-) were significantly higher than neonates of normotensive mothers (P<0.0001 and P<0.002, respectively).Newborns of smokers had significantly higher blood pressures too (P<0.02). Conclusion: Mother's blood pressure can affect neonatal blood pressure. Chronic hypertension, pre-eclampsia, and cigarette smoking in mothers can adversely alter neonatal blood pressure. These maternal conditions should be screened and managed as soon as possible.